Effect of Blanched Pineapple and Massage Therapy on Uterine Involution and Breast Milk Production: A Quasi-Experimental Study in Postpartum Mothers - Aryani, Yeni; Yustita, Annisa Tri (Chakra Brahmanda Lentera Institute, 2025)
Background: Optimal postpartum recovery and lactation are vital for maternal and neonatal health. Pineapple, rich in bromelain and bioactive compounds, may aid uterine involution and lactogenesis, while massage therapy promotes oxytocin release and milk production. Evidence on their combined effect remains limited. This study examined the impact of blanched pineapple consumption with massage therapy on uterine fundal height reduction and breast milk production in postpartum mothers. Methods: A quasi-experimental study with a two-group pretest–posttest design followed the TREND reporting guideline. 50 postpartum mothers were recruited using purposive sampling (25 intervention, 25 control). Inclusion criteria included mothers within 24–48 hours postpartum, aged 20–35 years, with a singleton birth and no obstetric complications; exclusion criteria were allergy to pineapple, postpartum hemorrhage, or medical contraindications for massage. The intervention group received blanched pineapple consumption (200 g/day for 7 days) combined with standardized massage therapy, while the control group received routine postpartum care. UFH was measured using a non-elastic tape, and breast milk production was assessed through maternal report and expressed volume (validated measurement protocol). Ethical approval was obtained from the institutional review board. Data were analyzed using paired and independent t-tests, and effect sizes (Cohen’s d, 95% CI) were calculated. Results: Mothers in the intervention group experienced a significantly greater reduction in UFH (mean difference = 2.1 cm, p < 0.01, Cohen’s d = 0.78) compared to the control group. Breast milk production was also higher in the intervention group, both in average volume (+45 mL/day, p < 0.01, Cohen’s d = 0.72) and frequency of breastfeeding episodes (OR = 2.3, 95% CI: 1.4–3.8). These findings indicate a synergistic effect of pineapple’s enzymatic properties and massage-induced oxytocin release on uterine involution and lactogenesis. Conclusion: Blanched pineapple consumption combined with massage therapy effectively accelerates uterine involution and enhances breast milk production in postpartum mothers. This integrated, non-pharmacological approach can be considered a safe and culturally adaptable adjunct to routine postpartum care. Healthcare providers are encouraged to incorporate such interventions into maternal recovery programs to support exclusive breastfeeding and improve maternal health outcomes.